Effect of Motivation and Perception of Farmers Response to Sugarcane Management Consolidation Program Plan - Mohamad Cholidi; Irham Irham; Lestari Rahayu Waluyati (Agro Ekonomi, 2020)
This study aimed to analyze (1) the difference levels of motivation, perception and behavioral responses of sugar cane farmers with irrigated land and rainfed land to the cane grower management consolidation plan, and (2) the effect of motivation and perception on farmers' behavioral responses related to the cane grower management consolidation plan. The research location was in the sugar factories of PT Perkebunan Nusantara XI. The samples consisting of sugar cane farmers with irrigated land and rainfed land who were randomly selected, amounting to 242 respondents. Novelty of research, there are object and analytical methods. The difference levels of motivation, perceptions and behavioral responses of farmers with irrigated land and rainfed land were analyzed by independent sample t-test. The influence of perception and motivation on the behavioral response of farmers to the cane grower management consolidation plan was analyzed by multiple linear regression. The results showed that, the level of motivation and perceptions of sugar cane farmers there were differences between farmers with irrigated land and rainfed land. Meanwhile, in terms of the response of farmers, there was no significant difference between irrigated land and rainfed land. The influence of motivation, perception, education, dummy variables of Purwodadi and Pradjekan sugar factories significantly influenced farmers' behavioral responses to the cane grower management consolidation plan. To improve the behavioral response of farmers, it is necessary to provide supervision regarding the management of cane grower and the benefits that farmers will obtain from the program to make farmers interested in understanding the objectives of the program.